Educational intervention for women in Japan coming of age for cervical cancer screening who grew up during the suspended HPV-vaccination-program - Ai Miyoshi; Yutaka Ueda; Asami Yagi; Toshihiro Kimura; Eiji Kobayashi; Kosuke Hiramatsu; Satoshi Nakagawa; Tadashi Kimura (Taylor & Francis Group, 2021)
Girls born in 2001 became eligible for subsidized HPV vaccination when they reached 12 years old in 2013, but that was the year when the Japanese MHLW suspended its official governmental recommendation for HPV vaccination. Those girls will now reach 20 years of age this year, 2021, and they will become eligible for cervical cancer screening. We report on the effects of an educational intervention with an information sheet about their current unvaccinated defenselessness for HPV and the necessity for early and repeated cervical cancer screening as a way to improve their intention to have that screening and their attitude toward HPV vaccination. Among the educated women, 75.2% had a positive intention toward having cervical cancer screening, 24.8% had a negative intention. Educational intervention can significantly promote the intention of having cervical cancer screening in women who had experienced the suspension of the MHLW's official recommendation for HPV vaccination. As a result of this simple intervention, they were more likely to think that HPV vaccination was needed for themselves.